Anillin forms linear structures and facilitates furrow ingression after septin and formin depletion - Lebedev, Mikhail; Chan, Fung-Yi; Lochner, Anna; Bellessem, Jennifer; Osório, Daniel S.; Rackles, Elisabeth; Mikeladze-Dvali, Tamara; Carvalho, Ana Xavier; Zanin, Esther (Cell Reports, 2023)
During cytokinesis, a contractile ring consisting of unbranched filamentous actin (F-actin) and myosin II constricts at the cell equator. Unbranched F-actin is generated by formin, and without formin no cleavage furrow forms. In Caenorhabditis elegans, depletion of septin restores furrow ingression in formin mutants. How the cleavage furrow ingresses without a detectable unbranched F-actin ring is unknown. We report that, in this setting, anillin (ANI-1) forms a meshwork of circumferentially aligned linear structures decorated by non-muscle myosin II (NMY-2). Analysis of ANI-1 deletion mutants reveals that its disordered N-terminal half is required for linear structure formation and sufficient for furrow ingression. NMY-2 promotes the circumferential alignment of the linear ANI-1 structures and interacts with various lipids, suggesting that NMY-2 links the ANI-1 network with the plasma membrane. Collectively, our data reveal a compensatory mechanism, mediated by ANI-1 linear structures and membrane-bound NMY-2, that promotes furrowing when unbranched F-actin polymerization is compromised.
Created from Fastlane, Scopus look-up
Keywords: actin; anillin; C. elegans; cell division; contractile ring; CP: Cell biology; cytokinesis; formin; intrinsically disordered; liquid-liquid phase separation; myosin